L’observation ethnographique en sociologie des rapports sociaux : sexe, race, classe et biais essentialistes - Xavier Dunezat (Sociologies, 2015)
This paper examines the essentialist biases which structure my practice of participant-observation in the mobilizations of unemployed people and undocumented migrants. On the one hand, it reveals the distortion between a “methodological constructivism” required to analyze the dynamics of class relations and forms of “methodological essentialism” allowable so as to apprehend the dynamics of gender and race relations. On the other hand, it calls for a constructivist leap in the methodology of ethnographic observation when it takes as a theoretical framework the sociology of social relations and their inter-connections.